2020
DOI: 10.1021/acs.orglett.0c03565
|View full text |Cite
|
Sign up to set email alerts
|

Zelkovamycins B–E, Cyclic Octapeptides Containing Rare Amino Acid Residues from an Endophytic Kitasatospora sp

Abstract: Four unusual cyclopeptides, zelkovamycins B–E (1–4), were isolated from an endophytic Kitasatospora sp. Zelkovamycin B was featured by an unprecedented 3-methyl-5-hydroxy­pyrrolidine-2,4-dione ring system linked to the cyclopeptide skeleton. Their structures and full configurations were established by spectroscopic analysis, Marfey’s method, and NMR calculations. A plausible biosynthetic pathway for zelkovamycins was proposed based on gene cluster analysis. Zelkovamycin E displayed potent inhibitory activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…It has also been shown that Streptomyces genomes are recombinogenic, with a high recombination rate exceeding those observed within many other bacterial species ( Doroghazi and Buckley, 2010 ). As the sister genus of Streptomyces , Kitasatospora has gradually attracted people’s attention ( Hao et al, 2020 ; Kim et al, 2020 ; Yun et al, 2020 ). So far, at least 50 bioactive compounds have been discovered from Kitasatospora strains ( Takahashi, 2017 ), such as setamycin, kitasetaline, and satosporin ( Ōmura et al, 1981 ; Aroonsri et al, 2012 ; Arens et al, 2013 ), exhibiting a wide range of bioactivities (e.g., antifungal, herbicidal, antitumor).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that Streptomyces genomes are recombinogenic, with a high recombination rate exceeding those observed within many other bacterial species ( Doroghazi and Buckley, 2010 ). As the sister genus of Streptomyces , Kitasatospora has gradually attracted people’s attention ( Hao et al, 2020 ; Kim et al, 2020 ; Yun et al, 2020 ). So far, at least 50 bioactive compounds have been discovered from Kitasatospora strains ( Takahashi, 2017 ), such as setamycin, kitasetaline, and satosporin ( Ōmura et al, 1981 ; Aroonsri et al, 2012 ; Arens et al, 2013 ), exhibiting a wide range of bioactivities (e.g., antifungal, herbicidal, antitumor).…”
Section: Introductionmentioning
confidence: 99%
“…Following the completion of this work and during the preparation of this manuscript, the isolation of zelkovamycin and its four analogues zelkovamycin B-E from Kitasatospora sp. CPCC204717 [ 62 ] was reported. In this study, a putative biosynthetic cluster for the five peptides was proposed, which largely agrees with the model described in the present work.…”
Section: Resultsmentioning
confidence: 99%
“…Mueller-Hinton medium (0.6% beef extract, 1.75% acid hydrolysate of casein, 0.15% starch) as described previously. 17 Cytotoxicity Assay. Cell viability was evaluated by using the Cell Counting Kit-8 (CCK8, Meilunbio, China) assay as described previously.…”
Section: ■ Associated Contentmentioning
confidence: 99%
“…Co-culturing different microbes in a single environment is an effective approach to enhance the chemical diversity of metabolites. Co-cultivation (also called mixed fermentation) can create a competitive environment, which may activate silent secondary metabolism genes and lead to the biosynthesis of bioactive products responsible for chemical defense. An increasing number of co-culture experiments have led to the discovery of new antimicrobials or to enhanced accumulation of metabolites even in the absence of viable bacterial cells. The study by Mearns-Spragg et al showed that (co-)­cultivation of marine microorganisms with live or dead bacteria both could stimulate the production of antimicrobial activity, and in most cases there was no difference in antimicrobial activity induced by live and dead cells . As a part of our ongoing search for new antimicrobials, we carried out (co-)­cultivation experiments of sponge-derived fungi with different live bacteria ( Escherichia coli and Bacillus subtilis ), actinomycetes, and other fungi or with autoclaved Pseudomonas aeruginosa , to elicit the production of fungal metabolites. Because P. aeruginosa is an opportunistic pathogen, the use of heat-killed P. aeruginosa in the mixed cultivation can offer a safe experimental condition and also reduce interexperiment variation. , Herein, we report the identification of six new peptaibols ( 1 – 6 ) and five known compounds from the sponge-associated fungus Acremonium sp.…”
mentioning
confidence: 99%